The collection of potato cultivars as a source for breeding for high yield, earliness, and resistance to late blight, virus diseases and Globodera rostochiensis Woll - L. I. Kostina; O. S. Kosareva (Труды по прикладной ботанике, генетике и селекции)
Background. The article presents information on the results of screening potato cultivars for major commercial traits: earliness, high yield, high starch content, resistance to late blight (Phytophthora infestans (Mont.) de Bary), virus diseases and potato nematode (Globodera rostochiensis Woll. (Ro1)). Materials and methods. VIR’s collection of domestic and foreign potato cultivars served as the material for this research. The study was conducted in accordance with the guidelines developed at the Potato Genetic Resources Department of VIR. Results and conclusion. The analysis of pedigrees helped to select source material for the main trends of domestic potato breeding. Data of a number of cultivars identified by analyzing progenies from self-pollination are presented in the paper. Potential sources of major commercial traits were found: cvs. ‘Banba’ (k-25222), ‘Bastion’ (k-25198), ‘Belukha’ (k-25146), ‘Charoit’ (k-25221), ‘Colleen’ (k-25224), ‘Gala’ (k-25270), ‘Geyzer’ (k-25266), ‘Gornyak’ (k-25311), ‘Larets’ (k-25211), ‘Leoni’ (k-25244), ‘Manifest’ (k-25265), ‘Meteor’ (k-25212), ‘Nur-Alem’ (k-25253), ‘Prizer’ (k-25217), etc. were identified as high yield sources; cvs. ‘Aktyubinskiy-2’ (k-25300), ‘Alaya roza’ (k-25144), ‘Charaўnik’ (k-25139), ‘Darnitsa’ (k-25179), ‘Lad’ (k-25180), ‘Levada’ (k-25121), ‘Maksimum’ (k-25136), ‘Palitra’ (k-25123), ‘Tamyz’ (k-25307), ‘Universal’ (k-25137), ‘Vektor’ (k-25200), ‘Vytok’ (k-11897), ‘Zarevo’ (k-10773) and ‘Zholbarys’ (k-25155) as sources of high starch content; cvs. ‘Aral’ (k-25107), ‘Aymurat’ (k-25248), ‘Bastion’ (k-25198), ‘Berkut’ (k-25250), ‘Gastsinets’ (k-25264), ‘Musinskiy’ (k-25312), ‘Nur-Alem’ (k-25253), ‘Rapsodiya’ (k-25130), ‘Senim’ (k-25306), ‘Sunkar’ (k-25258), ‘Tamyz’ (k-25307), ‘Udovitskiy’ (k-25260), ‘Vektor’ (k-25200), ‘Velikan’ (k-25201), ‘Zholbarys’ (k-25155) and ‘Zvezdochka’ (k-25209) as sources of late blight resistance; cvs. ‘Adil’ (k-25112), ‘Azart’ (k-25196), ‘Bastion’ (k-25198), ‘Charoit’ (k-25221), ‘Favorit’ (k-25132), ‘Gastsinets’ (k-25264), ‘Geyzer’ (k-25266), ‘Krasavchik’ (k-25210), ‘Maksimum’ (k-25136), ‘Malyshok’ (k-25189), ‘Manifest’ (k-25265), ‘Nadezhda’ (k-25213), ‘Nur-Alem’ (k-25253), ‘Pamyati Lorkha’ (k-25214), ‘Rapsodiya’ (k-25130), ‘Senim’ (k-25306), ‘Sirenevyy tuman’ (k-25143), ‘Sultan’ (k-25131), ‘Shchedrik’ (k-25126), ‘Tekes’ (k-25173), ‘Velikan’ (k-25201), ‘Volat’ (k-25263), ‘Zhemchuzhina’ (k-25128), etc. as sources of field resistance to virus diseases. Cultivars combining resistance to potato cyst nematode (Globodera rostochiensis Woll. (Ro1)) with other valuable commercial traits were also identified.